Human Bots and Algorithmic Bots in Tanzanian Politics: A Rising Threat to Democratic Discourse - Mlwale, Husna Juma; Mlodi, Lodgar Gabriel (Advances in Psychological Sciences and Applications, 2025)
The emergence of bot farms, both algorithmic and human-operated, poses a critical challenge to democratic discourse in many African nations, including Tanzania. Political actors are increasingly deploying these bot farms to manipulate public opinion, hijack political conversations, and create artificial consensus on sensitive national issues. This paper investigates the influence of such bots on political communication, focusing on recent patterns observed across Tanzanian digital platforms. It explores how both algorithmic and human bots are systematically employed to flood social media with curated content, silence opposition voices, and shape electoral narratives. Through qualitative analysis of digital interactions and secondary sources, this study reveals the strategic use of bots to manipulate political narratives, promote astroturfing, and suppress dissent. The paper highlights the implications for digital democracy, including the erosion of authentic political engagement, and emphasizes the urgent need for regulatory, civic, and technological responses to preserve democratic integrity in digital spaces.